Exploring global health diplomacy in Iran: insights from experts in health and foreign policy - Amirhossein Takian; Jalal Arabloo; Mohsen Asadi-Lari; Ebrahim Jaafaripooyan; Sanaz Taghizade; Mohammad Javad Zarif (BMJ Global Health)
Introduction The literature on global health diplomacy (GHD) is scarce, particularly in the context of low- and middle-income countries (LMICs). This study thus explores the GHD concept, content, policy-making process and influencing factors in Iran from the perspectives of key health and foreign policy-makers.Methods This is a qualitative study using conventional content analysis. We conducted in-depth, semi-structured interviews with 29 experts from the health and diplomatic sectors in Iran, supplemented by five focus group discussions. We used purposeful and snowball sampling techniques to identify key informants and continued data collection until saturation was achieved. Data analysis was facilitated by MAXQDA V.12 software.Results A lack of consensus emerged among the health and foreign policy-makers regarding the definition and importance of GHD, and the varying interpretations of the concept were influenced by the level of knowledge, personal experiences and professional backgrounds, values and belief systems of participants. GHD was found under a relative influence of—both explicit and implicit—ideological and political challenges in Iran. The excessive emphasis on the ideological aspects and the dominance of political, security and military considerations over other foreign policy objectives have been identified as a major barrier to achieving the desired policy goals. Health integration into foreign policy has often been reactive and crisis-driven, rather than planned and proactive, failing to adequately identify or optimise available domestic and international opportunities. Additionally, participants singled out the lack of an inter-sectoral institution or steering council to improve policy coherence and enhance coordination across and within sectors.Conclusion A common understanding of GHD is expected to pave the way for the implementation and effective achievement of broader foreign and health policy goals in LMICs, such as Iran.